2015
DOI: 10.1007/s00500-015-1741-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design of fractional-order PID controller for five bar linkage robot using a new particle swarm optimization algorithm

Abstract: This paper introduces a new version of the particle swarm optimization (PSO) method. Two basic modifications for the conventional PSO algorithm are proposed to improve the performance of the algorithm. The first modification inserts adaptive accelerator parameters into the original velocity update formula of the PSO which speeds up the convergence rate of the algorithm. The ability of the algorithm in escaping from local optima is improved using the second modification. In this case, some particles of the swar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 26 publications
(26 reference statements)
0
34
0
Order By: Relevance
“…If the closed loop system becomes unstable, then the cost function is penalized by a significant value. The fractional PID controller was also tested for robustness against uncertainties of the model parameters and the same method was used for designing the fractional controller for a five bar linkage robot [95] .…”
Section: Methodsmentioning
confidence: 99%
“…If the closed loop system becomes unstable, then the cost function is penalized by a significant value. The fractional PID controller was also tested for robustness against uncertainties of the model parameters and the same method was used for designing the fractional controller for a five bar linkage robot [95] .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the exploitation occurs when these two values are both small. PSO has attracted wide attention in control engineering design problems due to its algorithmic simplicity and powerful search performance [62], [63]. However, PSO algorithm that requires a large number of fitness evaluations before locating the global optimum is often prevented from being applied to computationally expensive real-world problems [64].…”
Section: Particle Swarm Optimizer (Pso)mentioning
confidence: 99%
“…Numeric values of the parameters of the five-bar manipulator dynamics are taken from [62], [90] as shown in Table 1. From the data driven in Table 1, it is revealed that The search procedure for the robust optimal result is done in the ranges as [62]: Moreover, according to an updated set of training samples, a new GP surrogate is constructed after each sequential EI iteration.…”
Section: Dynamics Of Five-bar Linkage Robot Manipulatormentioning
confidence: 99%
See 1 more Smart Citation
“…In [56] authors presented the optimal trajectory tracking control of robotic manipulator using an ACO algorithm based PID controller. An optimal design of PID using particle swarm optimization algorithm (PSO) for the control of five bar linkage robot has been introduced in [57]. A PSO algorithm for fuzzy predictive control has been developed and applied for quadrupletank process in [58].…”
Section: Introductionmentioning
confidence: 99%